2014
DOI: 10.1037/a0035191
|View full text |Cite
|
Sign up to set email alerts
|

The role of moral emotions in the development of children’s sharing behavior.

Abstract: This study investigated the role of moral emotions in the development of children's sharing behavior (N = 244 4-, 8-, and 12-year-old children). Children's sympathy was measured with both self- and primary caregiver-reports, and participants anticipated their negatively and positively valenced moral emotions (i.e., feeling guilty, sad, or bad; and feeling proud, happy, or good) following actions that either violated or upheld moral norms. Sharing was measured through children's allocation of resources in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 67 publications
10
78
4
4
Order By: Relevance
“…Younger children also tend to keep even more resources than older children (e.g. Benenson et al, 2007), and younger children are found to keep all of the resources more frequently than older children (Blake & Rand, 2010;Gummerum et al, 2010;Ongley & Malti, 2014). However, in the present study few children kept all the stickers, and the most common distribution pattern was to divide the stickers equally between themselves and the other child.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Younger children also tend to keep even more resources than older children (e.g. Benenson et al, 2007), and younger children are found to keep all of the resources more frequently than older children (Blake & Rand, 2010;Gummerum et al, 2010;Ongley & Malti, 2014). However, in the present study few children kept all the stickers, and the most common distribution pattern was to divide the stickers equally between themselves and the other child.…”
Section: Discussioncontrasting
confidence: 45%
“…Resource distribution tasks like the Dictator Game (DG) have been used to examine fairness and prosocial behavior in young children (Aguilar-Pardo, Martínez-Arias, & Colmenares, 2013; Benenson, Pascoe, & Radmore, 2007;Benozio & Diesendruck, 2015;Blake & Rand, 2010;Chen, Zhu, & Chen, 2013;Gummerum, Hanoch, Keller, Parsons, & Hummel, 2010;Kogut, 2012;Lucas, Wagner, & Chow, 2008;Ongley & Malti, 2014) and typically generate greater variation in responses than binary forced-choice measures. Blake and Rand (2010) have also successfully used the DG to demonstrate that children use their own a priori explicitly stated preferences to guide how they distribute resources.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies have shown that preschoolers who had passed ToM tests shared resources more generously with others (Rochat et al, 2009;Takagishi, Kameshima, Schug, Koizumi, & Yamagishi, 2010;Wu & Su, 2014) and evaluated unequal sharing as less acceptable compared with children who had not passed ToM tests (Mulvey, Buchheister, & McGrath, 2016). In addition, higher levels of sympathy in 4-year-old children were associated with larger amounts of sharing in dictator games (Ongley & Malti, 2014). However, ToM was also found to be unrelated to children's performance in sharing games (Lucas et al, 2008;Mulvey et al, 2016) and was even related to less sharing because children with ToM might know there were no consequences for not sharing (Cowell, Samek, List, & Decety, 2015).…”
Section: Altruism and Theory Of Mindmentioning
confidence: 93%
“…Coding Our coding method was adapted from past research on children's guilt Ongley and Malti 2014). First, anticipated emotions following Question 1 were coded as 1 (guilt-related emotion) or 0 (not guilt-related emotion).…”
Section: Methodsmentioning
confidence: 99%